Karakteristik dan Fungsi Puisi Arab pada Masa Transisi Pemerintahan Dinasti Umayyah ke Dinasti Abbasiyah - Najmah Al Hinduan; Achmad Tohe; Ibnu Samsul Huda (Universitas Islam Negeri Walisongo Semarang - Indonesia, 2020)
The transition period of the Umayyad dynasty to the Abbasid dynasty occurred in a span of 100 years. There are fifteen great poets whose poetry represents the study of this research. The results of this study indicate that there are seven types of poetry found in the transition period, namely madh, hija, naqaidh, zuhud, gazal, khamriyyat, and fakhr. These seven poems have different characteristics to fulfill different functions. Among them are diction which uses connotative words, strong imagination, uses a lot of simile/tasybih, cynicism, sarcasm, personification, and metaphor/istia'rah.